Neuroprotective oleanane triterpenes from the roots of Bupleurum chinense. Issue 6 (15th March 2016) - Li, Dan-Qi; Zhou, Le; Wang, Di; Wu, Jie; Li, Ling-Zhi; Huang, Xiao-Xiao; Liu, Qing-Bo; Wu, Ying-Ying; Lin, Song; Yang, Jing-Yu; Song, Shao-Jiang; Wu, Chun-Fu
Graphical abstract: Abstract: The discovery of new natural compounds with pharmacological properties is an increasingly important field, and a continuous phytochemical investigation of the roots of Bupleurum chinense D.C. has led to the isolation of17 triterpenoids, including three new oleanane triterpenes (1 –3 ) together with14 known ones. Their structures were determined on the basis of 1D and 2D NMR spectra as well as HR-ESI-MS data. The cytotoxicities of all compounds against five selected human cancer cell lines were assayed. Only compounds9 and14 exhibited moderate activities. Recently, a number of investigations have focused on the neuroprotective properties of triterpenoids in B. chinense . In order to expand our knowledge about this herb, the neuroprotective effects of compounds1 –17 against hydrogen peroxide (H2 O2 )-induced neuronal cell damage in human neuroblastoma SH-SY5Y cells were evaluated. Compounds1 –3, 6 –7 showed significant neuroprotective effects against H2 O2 -induced SH-SY5Y cell death. Preliminary structure–activity relationships (SARs) between neuroprotective effects and the isolates were also discussed.